The Relationship Between Parity to Placental Retention and The Impact on Days Open and Calving Intervals in Dairy Cows at KPSBU Lembang - HAFILAH, IDZNI; Septiyani, Septiyani; Solihati, Nurcholidah (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
Placental retention or retensio secundinae is one of the reproductive disorders that often occurs in dairy cows. This will interfere reproductive efficiency, including Days Open and Calving Interval. Retained placenta is defined as the failure to completely pass all of the placenta from the uterus (cotyledon villi) for more than 8 hours after parturition. This study aimed to determine the relationship between parity and placental retention and its impact on lambing days and lambing distance in dairy cows. The research was conducted at North Bandung Cattle Farming Cooperative (KPSBU) Lembang. The method used was data analysis using descriptive analysis and path analysis. The results showed that parity has a significant relationship with placenta retention, and placenta retention with increasing parity can affect days open and calving interval in dairy cows at KPSBU Lembang. Path analysis found that the t-statistical results had exceeded 1.96 with a significant p-value that did not exceed 0.05, so there was a significant relationship between the variables in the study. Dairy cows that have experienced retained placenta at North Bandung Cattle Farming Cooperative (KPSBU) Lembang have low reproductive efficiency, characterized by long open days and calving intervals exceeding the expected time.